logx-log6=2
log(x/6)=2
x/6=10^2
x=6*10^2
x=600
2007-07-26 11:33:08
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
logx - log6 = 2 remember log is using base ten
and logx - log6 = log (x/6) and antilog2 = 10^2
So, moving right along we have
x/6 = 10^2
x = 600
You enjoy the rest of your Summer
2007-07-26 10:50:24
·
answer #2
·
answered by obidic 1
·
0⤊
0⤋
quoitent rule:
log a - log b = log (a/b)
logx - log6 = 2
log (x/6) = 2
change to exponent form: log_b a = x <--> b^x = a
10^2 = x/6
x = 6 x 10^2
x = 600
2007-07-26 10:43:12
·
answer #3
·
answered by 7
·
0⤊
0⤋
There are a couple of ways of going about this. You could combine the logs, then use the defintion of log to rewrite the expression as an exponent.
log(x) - log(6) = 2
log(x/6) = 2
This means (x/6) = 10^2
So x/6 = 100, meaning x = 600
2007-07-26 10:42:46
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Assume logs are to base 10.
log (x / 6) = 2
x / 6 = 10²
x / 6 = 100
x = 600
2007-07-26 10:42:43
·
answer #5
·
answered by Como 7
·
1⤊
0⤋
Hey there!
Here's the answer.
log(x)-log(6)=2 --> Write the problem.
log(x/6)=2 --> Use the quotient property of logarithms i.e. log(m)-log(n)=log(m/n).
x/6=10^2 --> Use exponential-logarithmic inverse properties i.e. 10^log(x)=x. Make the base on each side of the equation 10.
x/6=100 --> Change 10^2 into 100.
x=600 Multiply 6 on both sides of the equation.
So the answer is x=600.
Hope it helps!
2007-07-26 11:04:44
·
answer #6
·
answered by ? 6
·
0⤊
1⤋
log(x/6)=2
(x/6)=10^2
x/6=100
x=600
salamat
2007-07-26 10:42:28
·
answer #7
·
answered by 037 G 6
·
0⤊
0⤋